2022
DOI: 10.1038/s41598-022-20417-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and NGS predictors of response to regorafenib in recurrent glioblastoma

Abstract: Predictive factors for response to regorafenib in recurrent glioblastoma, IDH-wildtype, are scarcely recognized. The objective of this study was to identify molecular predictive factors for response to regorafenib using a clinically available platform. We analyzed a prospective cohort of 30 patients harboring recurrent glioblastoma, IDH-wildtype, and treated with regorafenib. Next-generation sequencing (NGS) analysis was performed on DNA extracted from paraffin-embedded tissues using a clinically available pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Santangelo and colleagues [ 12 ] identified five biomarkers which could help in identifying a subpopulation of GBM patients exhibiting a striking survival advantage when treated with regorafenib. Analogously, Chiesa et al [ 47 ] very recently published the results of an NGS study performed on a cohort of 30 GBM patients harboring recurrent glioblastoma and treated with regorafenib. They identified two different mutations which seem to be associated with a poor response to regorafenib: a mutation in the EGFR pathway and a mutation in the mitogen-activated protein-kinase (MAPK) pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santangelo and colleagues [ 12 ] identified five biomarkers which could help in identifying a subpopulation of GBM patients exhibiting a striking survival advantage when treated with regorafenib. Analogously, Chiesa et al [ 47 ] very recently published the results of an NGS study performed on a cohort of 30 GBM patients harboring recurrent glioblastoma and treated with regorafenib. They identified two different mutations which seem to be associated with a poor response to regorafenib: a mutation in the EGFR pathway and a mutation in the mitogen-activated protein-kinase (MAPK) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note, as a mere speculation, that GSC#83 are EGFRvIII-positive as opposed to GSC#1. In their recent paper, Chiesa and colleagues [ 47 ] identified EGFR pathway mutation as a characteristic associated with poor response to regorafenib in GBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research has identified molecular features correlated with prolonged survival rate in regorafenib-treated GBM patients. These features include EGFR mutations ( Chiesa et al, 2022 ), gene transcripts such as HIF1A and CDKN1A, miRNAs like miR-3607–3p, miR-301a-3p, miR-93–5p ( Santangelo et al, 2021 ), and MAPK pathway mutations that may associate with a poor prognosis ( Chiesa et al, 2022 ). However, limited evidence restricts the scope of individualized dosing of regorafenib, hence, greater evidence is required to increase its widespread acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated DNA sequencing and copy number analysis have identified potential driver genes, and molecular profiling, as demonstrated by several clinical sequencing efforts, not only provides insights into glioma biology, but also offers multi‐level solutions, including the development of novel small molecule drugs 7,8 . Targeted sequencing is the selection of mostly established cancer genes for targeted sequencing of the disease to facilitate the selection of the most likely responders to certain anticancer drugs 9 . Deep targeted sequencing of tumor samples is becoming increasingly valuable and its application in the clinic deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%